Discharge of suspended solids and radiocesium into stream water in a forested watershed before and after line thinning with spur road construction. (December 2020) - Shinomiya, Yoshiki; Kobayashi, Masahiro; Tsurita, Tatsuya; Tsuboyama, Yoshio; Sawano, Shinji; Itoh, Yuko; Ohnuki, Yasuhiro; Shichi, Koji
Abstracts: In an experimental watershed located around 120 km southwest of the Fukushima Daiichi Nuclear Power Plant with a drainage area of 59.9 ha, suspended solids (SS) and radioactive cesium discharge from a forested headwater catchment were monitored before and after line thinning. The lower slopes in the experimental watershed were covered with plantation conifer trees (Japanese cedar), while the upper slopes were covered with deciduous trees. In 2012, line thinning was carried out at a thinning rate of 35% across 17% of the northeastern part of the watershed and across the remaining part in 2013. Spur roads were constructed along all tributaries without water, and logged trees were dragged and grappled using forestry machinery and transported along these roads to timber yards using forwarder-type forestry vehicles. A V-notch weir and a water level gauge were installed at the watershed outlet and stream water was sampled twice a month during base flow, whereas during flood flow, stream water samples of 1 L were collected every hour using an automatic water sampler. These samples were filtered through 0.5 μm glass fiber filters to measure the SS concentration. SS concentration data was collected for 21 floods before thinning and for 37 floods after thinning. A time-integrated SS sampler was installed in the stream close to the weir and SS samples were collected every two or three months to measure their Cs-137 concentrations. SS concentrations before (from July 2010 to August 2012) and after thinning (from October 2013 to December 2018) were compared, where the maximum SS concentrations before and after thinning were 211 and 790 mg L −1, respectively. It was discovered that some SS concentrations during flood flow were higher after carrying out thinning than before. Some ΣLss values (specific cumulative load of SS in a flood event) also showed the same results as the SS concentrations. Thus, it was clear that SS discharge immediately increases after thinning, but as it increases Cs-137 export is limited. This is related to a change in SS source brought about by the process of thinning, a decrease with time in the Cs-137 concentration in organic solid expected from that in litter, and a regrowth of vegetation on spur roads, protecting them against soil erosion. Therefore, it was concluded that thinning does not drastically increase Cs-137 export from a forested watershed. Highlights: Cs-137 export in suspended solid (SS) was monitored in a thinned forested watershed. Suspended solids (SS) discharge increased after thinning. Cs-137 concentration in the SS declined after thinning. Thinning does not drastically increase Cs-137 export from a forested watershed.